Why do women attend writing retreats?. Issue 8 (16th November 2020) - Murray, Rowena; Kempenaar, Larissa
ABSTRACT: Inequality in academic careers is structural and systemic. However, the growing writing retreat movement offers alternative structures for academic work, and in many countries retreats are mostly attended by women. We asked women about their experiences of retreats and did a systems and transactional analysis of their appraisals of writing and perceptions of relationships with systems at work. This article provides some answers to the question of why writing retreats are attractive to and seem to benefit women. A Structured Writing Retreat is one place where women can develop process, performance, prospect and profit beliefs in relation to their writing by creating a microsystem that sustains those beliefs. However, ambivalence in responses – in relation to research assessment, management and teaching overload – is a reminder of the overarching systems in which they work. This research shows that some women can counter some discriminatory practices, some of the time, at writing retreats.